An Approach Based on Partial Executions for Evaluating the Scalability of Parallel Applications - Maia, Reilta Christine Dantas; Xavier-de-Souza, Samuel (Anais da Escola Regional de Alto Desempenho da Região Nordeste (ERAD-NE), 2025)
Scalability analysis is crucial for developers to gauge how their applications perform under varying resource and workload conditions. However, analyzing complex applications can be time-consuming. This study proposes a partial execution approach in the Parallel Scalability Analyzer tool, leveraging the Paramount Iteration technique. This approach holds significant potential for reducing scalability analysis time.